Colchicine Increases Ventricular Vulnerability in an Experimental Whole‐Heart Model. Issue 5 (5th January 2017) - Frommeyer, Gerrit; Krawczyk, Julius; Dechering, Dirk G.; Kochhäuser, Simon; Leitz, Patrick; Fehr, Michael; Eckardt, Lars
Abstract: The traditional gout medication colchicine has been reported to effectively prevent atrial fibrillation recurrence after atrial fibrillation ablation or cardiac surgery in a few clinical trials. Severe adverse events have not yet been reported. The aim of the present study was to assess possible direct electrophysiological effects in an experimental whole‐heart model. Ten rabbit hearts were isolated and Langendorff‐perfused. Thereafter, colchicine was administered in two concentrations (1 and 3 μM). Eight endo‐ and epicardial monophasic action potentials and a 12‐lead ECG showed a stable QT interval and action potential duration during colchicine infusion. Furthermore, there was no significant increase in dispersion of repolarization. However, colchicine induced a dose‐dependent significant decrease of effective refractory period (ERP; 1 μM: −19 ms, 3 μM: −22 ms; p < 0.05). In the present study, acute infusion of colchicine in isolated rabbit hearts resulted in a reduction of ERP in the presence of a stable myocardial repolarization. This led to a significantly elevated inducibility of ventricular fibrillation. In 4 of 10 hearts, incessant ventricular fibrillation occurred. These results suggest a pro‐arrhythmic or toxic effect of colchicine and underline that further clinical studies on potential adverse effects should be conducted before the drug can be recommended for routine use after atrial fibrillation ablation.